Contractor’s Perception of the Use of Statistical Approach in the Tender Process at the Public Works Department, Malaysia - Muhamad Halil, Faridah (2006)
Contractor selection is one of the main activities of clients. Without a proper and accurate method for selecting the most appropriate contractor, the performance of the project will be affected. The usage of statistical method is implemented by Public Works Department as a better tool for the selection of suitable contractor. This method would avoid a personal preference during selection of contractor for government project. Furthermore, this method will ensure the price submitted by the tenderer is reflective of the current market conditions.